Enrobing Ceremony for Municipal Court Judge R. L. "Chip" Putnam in Jury Assembly Room - Watkins, Howard::::::::: (1987)
En Banc Court: front row: Justices George Brown, Donald Franson, Charles Hamlin, Hollis Best and Jay Ballantine; 2nd row: Judges Judge R. L. "Chip" Putnam, Nicholas Dibiaso, Ralph Nunez, James Quaschnick, Dennis Caeton, James Ardaiz; back row: Judges John "Nip" Gallagher, Buck Levis, Victor Papadakis, Joan McIntosh, Justice Thomas Harris, and Judge Gary Austin